Mikrogeschichten der Erinnerungskultur Am grünen Strand der Spree und die Remedialisierung des Holocaust by bullets - Saryusz-Wolska, Magdalena (Medien und kulturelle Erinnerung, 2022)
Who constructs memory culture? What kind of impact do conceptions of history have on their users? What kind of infrastructure activates cultural memory? In three microhistorical studies, this volume examines Through the Night as a novel, audio play, and TV series (1955-1960) to ask how memories of the mass shootings of Jews in the occupied Soviet Union during the Second World War circulated in the Federal Republic of Germany.